Semi-automatic control of network systems with non-monotonic Lyapunov function. Issue 8 (3rd August 2021) - Tran, Tri; Ha, Q. P.
Abstract : A partially decentralised scheme for the semi-automatic control of network systems with stabilising agents is presented in this paper. The semi-automatic control of interconnected systems employing the stabilising agent whose installation is segregated from the associated control algorithm has been presented previously. In this development, the quadratic dissipativity constraint (QDC) associated with a non-negative supply rate is newly introduced for the stabilising agent. The closed-loop system having bounded disturbances is input-to-state stabilised with a non-monotonic Lyapunov function when the QDC is used with model predictive controllers. The effectiveness of the QDC for stabilising agents in the presented partially decentralised architecture is demonstrated via simulation studies of a frequency regulation problem in power systems.